Designing immunostimulatory double stranded messenger RNA with maintained translational activity through hybridization with poly A sequences for effective vaccination. (January 2018) - Uchida, Satoshi; Yoshinaga, Naoto; Yanagihara, Kayoko; Yuba, Eiji; Kataoka, Kazunori; Itaka, Keiji
Abstract: Messenger (m)RNA vaccines require a safe and potent immunostimulatory adjuvant. In this study, we introduced immunostimulatory properties directly into mRNA molecules by hybridizing them with complementary RNA to create highly immunogenic double stranded (ds)RNAs. These dsRNA formulations, comprised entirely of RNA, are expected to be safe and highly efficient due to antigen expression and immunostimulation occurring simultaneously in the same antigen presenting cells. In this strategy, design of dsRNA is important. Indeed, hybridization using full-length antisense (as)RNA drastically reduced translational efficiency. In contrast, by limiting the hybridized portion to the mRNA poly A region, efficient translation and intense immunostimulation was simultaneously obtained. The immune response to the poly U-hybridized mRNAs (mRNA:pU) was mediated through Toll-like receptor (TLR)-3 and retinoic acid-inducible gene (RIG)-I. We also demonstrated that mRNA:pU activation of mouse and human dendritic cells was significantly more effective than activation using single stranded mRNA. In vivo mouse immunization experiments using ovalbumin showed that mRNA:pU significantly enhanced the intensity of specific cellular and humoral immune responses, compared to single stranded mRNA. Our novel mRNA:pU formulation can be delivered using a variety of mRNA carriers depending on the purpose and delivery route, providing a versatile platform for improving mRNA vaccine efficiency.